Tunable thermal transport and reversible thermal conductivity switching in topologically networked bio-inspired materials. Issue 10 (October 2018) - Tomko, John; Pena-Francesch, Abdon; Jung, Huihun; Tyagi, Madhusudan; Allen, Benjamin; Demirel, Melik; Hopkins, Patrick
Abstract The dynamic control of thermal transport properties in solids must contend with the fact that phonons are inherently broadband. Thus, efforts to create reversible thermal conductivity switches have resulted in only modest on/off ratios, since only a relatively narrow portion of the phononic spectrum is impacted. Here, we report on the ability to modulate the thermal conductivity of topologically networked materials by nearly a factor of four following hydration, through manipulation of the displacement amplitude of atomic vibrations. By varying the network topology, or crosslinked structure, of squid ring teeth-based bio-polymers through tandem-repetition of DNA sequences, we show that this thermal switching ratio can be directly programmed. This on/off ratio in thermal conductivity switching is over a factor of three larger than the current state-of-the-art thermal switch, offering the possibility of engineering thermally conductive biological materials with dynamic responsivity to heat. Thermal conductivity in a proteinaceous semi-crystalline material can be modulated by more than three times upon hydration and dehydration cycles.